The effect of mindfulness intervention on internet negative news perception and processing: An implicit and explicit approach - Yang, Ya; Su, Fang; Liu, Huan; Li, Xu (Frontiers in Psychology, 2023)
The internet facilitates the formation of the information society while also accelerating the viral spread of negative news and negative emotions, increasing public uncertainty and depression and impeding consensus, especially in the post-pandemic period. Mindfulness intervention, which has a positive effect on attention focus, self-regulation, and subjective wellbeing, is proven to mitigate negative emotional effects, and even alter mind patterns. The study aimed to give insight into the effect of mindfulness in the new media field, concerning trait mindfulness improvement, emotional arousal and regulation, and implicit attitudes from the perspective of intra-personal communication and positive communication. The study conducted a randomized pre-test–post-test control group design, with 3 (condition groups: mindfulness vs. placebo vs. control) × 2 (test times: pre vs. post). Participants who were exposed to negative news coverage with negative emotional arousal received 14 consecutive days of intervention. The results showed that mindfulness training can improve trait mindfulness effectively on the whole, especially in facets of describing, acting awareness, and non-judgment, and mitigate the negative effect from bad information coverage, while mindfulness intervention on mind patterns and expectations on controversial issues still awaited future empirical research. The present study intended to bridge the bonding between positive psychology and new media studies by focusing on individual attention improvement and negative emotion regulation, in the expectation that trait mindfulness can be beneficial in individual infodemic syndromes such as judgment bias and information exhaustion, and avoidance.